Geliat dan Keterpengaruhan Tafsir Alquran dalam Dakwah di Malaysia - Zakirman Zakirman; Shafwatul Bary (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2019)
The process of interpreting the Quran continues to evolve from Arabic to all corners of the world. Among other things, Malaysia. The Qur'anic interpretation in Malaysia dates back to the 17th century through oral para da'i. While the tradition of writing the Qur'anic interpretations only appeared in the 20th century. And as one way of transmitting Islamic values, the interpretation of the Quran in Malaysia took place in the da'i's preaching and under the influence of the previous interpreters. Recorded Abdurrauf as-Sinkily, Muhammad Abduh and Rasyid Ridha, and al-Maraghi were the most influential figures in interpreting the Quran and Islamic studies in Malaysia. This article will look at how the Qur'anic interpretations travel according to the way of transmission by the da'i, and how the influence of each character changes the order of interpretation in Malaysia. As a result, the process of interpreting the Quran in Malaysia was identified as growing through the hands of the da'is who were exposed to the ideology of their teachers, as well as the previous interpreters